A Distorted Wave T-Matrix Approach to Ionization of Atoms by Slow Heavy Particle Impact - Kh, Tsookhuu; J, Madsen (Scientific transaction of the National University of Mongolia. Physics, 2022)
We propose a theory for the description of slow inelastic collisions between charged particles and simple atomic systems based on a T-matrix approach. Using an eikonal distortion to describe the heavy particle motion, the T-matrix is obtained by the stationary phase approximation. In result, the ionization cross section is expressed by the product between the width of decay of the "quasimolecular" system formed during the collision and a surviving probability of the heavy particle in elastic channel.